AKHLAK DALAM KISAH TELADAN (AL-QUDWAH) NABI YA’QUB AS DAN APLIKASINYA DALAM KEHIDUPAN - HS, Nasrul; Dwi Andhika, Femas; Rahmi , Suci; Dwi Friana , Eva; Syahrani , Syalum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of prophetic role models in shaping Islamic morality, particularly the exemplary character of Prophet Ya'qub (Jacob) AS, which reflects the values of patience, trust in Allah (tawakkul), positive thinking toward Allah (husnuzan), and compassion. Amid the moral challenges faced by modern society, these values remain highly relevant and applicable in daily life. This study aims to describe the exemplary story (al-qudwah) of Prophet Ya'qub AS in the Qur'an, identify the moral values reflected in his life, analyze their implementation in everyday life, and explain their relevance to contemporary moral development. This research employs a qualitative approach using a library research method. Data were collected from the Qur'an, Qur'anic commentaries (tafsir), books, scholarly journals, and other relevant literature. The data were analyzed using content analysis and a thematic interpretation (maudhu'i) approach. The findings reveal that Prophet Ya'qub AS serves as a model of noble character through his extraordinary patience in facing trials, strong reliance upon Allah SWT, positive assumptions toward divine decree, and deep affection for his family. These values can be implemented in daily life through self-control, balancing effort with prayer, maintaining optimism, and fostering compassionate communication. Furthermore, the moral example of Prophet Ya'qub AS is highly relevant to the development of moral character in modern society and can serve as a solution to various moral and social problems.